Team Mental Models: Review, Analysis, and Integration - Rom, Eldad (Journal of Psychology and Psychotherapy Research, 2017)
In recent years an innovative sociocognitive perspective for exploring teamwork effectiveness has been advocated by numerous researchers. This perspective examines ways by which team members develop mutual understanding. The general idea is that team effectiveness will improve if team members hold adequately shared cognitive representations, often termed as team mental models. Although this theory has significant potential for explaining teamwork effectiveness, there are several conceptual inconsistencies that impede its developmental potency. The purpose of the current article is to review and integrate the accumulated knowledge, thus facilitating future theoretical and empirical work. The paper reviews interdisciplinary groundwork relating to team mental models, analyzes recent empirical findings, and develops a conceptual framework from which conclusions for future research are drawn.